Ru-M-coated Al-SiO2 catalyst as well as preparation method and application thereof
By adopting the Ru-M@Al-SiO2 catalyst with core-shell structure, the problems of large amount of precious metals and short life of existing catalysts are solved, and efficient and low-cost catalytic tetracarboxylate hydrogenation reaction is achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202311292783.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-10-08
AI Technical Summary
When the existing catalysts catalyzed the hydrogenation of tetramethyl phenylase tetramethyl phenylase esters, the precious metals are used in large quantities, high production costs, and short catalyst life, making it difficult to meet the needs of industrial production.
The Ru-M@Al-SiO2 catalyst adopts a core-shell structure, which consists of active component Ru, co-active component M and Al-SiO2 support. A microspherical structure is formed through a specific preparation method to reduce the amount of precious metals.
The hydrogenation reaction of tetracarboxylate phenylase tetracarboxylate is achieved with high activity and high selectivity, which reduces production costs and extends the life of the catalyst, making it suitable for industrial production.
Smart Images

Figure CN119771403A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a Ru-M@Al-SiO2 catalyst and a preparation method thereof, as well as application of the catalyst in catalyzing the synthesis of hydrogenated tetramethyl pyromellitic acid from tetramethyl pyromellitic acid. Background Art
[0002] Hydrogenated pyromellitic anhydride is an important organic synthesis intermediate and an intermediate for the development of new chemical materials and high value-added fine chemical products. It is mainly used in laboratory research and development processes and chemical production processes. At present, the main use of hydrogenated pyromellitic anhydride at home and abroad is to produce new engineering plastic polyimide (PI). The colorless and transparent polyimide (PI) prepared by the reaction of hydrogenated pyromellitic anhydride and aromatic diamine compounds such as p-diaminodiphenyl ether has excellent transparency and infusibility. It can be made into films, fibers, wire enamels, adhesives, laminates and molded parts, etc., and is called "golden film". It has broad application prospects in high-tech fields such as microelectronics, automobiles, optoelectronics, large-scale integrated circuits, flat panel displays, aerospace and semiconductor materials. For example: in the optical field, it is used as optical switch materials, passive or active waveguide materials, optical fibers, second-order nonlinear optical materials, optoelectronic packaging materials, photosensitive materials, filters, photorefractive materials and other related optoelectronic materials; in the electronics field, it is used as the substrate of organic electroluminescent displays (OLED), the substrate of liquid crystal displays, negative compensation films, liquid crystal orientation film materials, etc.; in the aerospace field, it is used for thermal control coating materials, antenna collector materials, antenna reflector materials, interlayer insulation films of solar panels, etc.
[0003] The key technology for the preparation of hydrogenated pyromellitic dianhydride is the preparation of hydrogenated pyromellitic acid. Hydrogenated pyromellitic acid is mainly prepared by catalytic hydrogenation of pyromellitic acid; or hydrogenation of pyromellitic ester to synthesize hydrogenated pyromellitic ester, and then hydrolyzing to obtain hydrogenated pyromellitic acid, which all belong to the category of hydrogenation of aromatic compounds and saturated hydrogenation of benzene rings.
[0004] EP1323700 uses pyromellitic acid as a raw material and 5% Rh / C catalyst for hydrogenation in an intermittent reactor. The catalyst has high initial activity and selectivity, but low reusability and must be frequently activated, which greatly increases production costs.
[0005] JP2006083080 and JP200863263 also use rhodium as an active component, but the life of the catalyst is short.
[0006] CN102105428 uses a mixed catalyst of palladium metal and rhodium metal to catalyze the hydrogenation of pyromellitic acid, but the reaction conditions are harsh and the required hydrogen pressure is at least 8 MPa, which puts forward high requirements on the reaction equipment and requires a large investment in equipment during industrialization.
[0007] CN104926649 uses Ru-Pd noble metal as an active component and Ce as an auxiliary agent loaded on activated carbon. The catalyst can effectively reduce the reaction pressure, but the reaction temperature is high and the amount of catalyst used is large, resulting in excessive initial investment costs.
[0008] Based on the existing technology, the synthesis of hydrogenated tetramethyl pyromellitic acid by hydrogenating tetramethyl pyromellitic acid and then hydrolyzing it to prepare hydrogenated pyromellitic acid has a higher yield. However, the current catalysts all use precious metals such as Rh, Pd, Pt, Ru, etc. as active components, and the amount of catalyst used is large, which is not conducive to industrial production.
[0009] Therefore, on the basis of ensuring catalytic activity, reducing the amount of precious metals by introducing non-precious metal additives is the future research direction of the hydrogenation reaction of tetramethyl pyromellitate. Summary of the invention
[0010] Purpose of the invention: The purpose of the present invention is to provide a core-shell structure Ru-M@
[0011] Al-SiO2 catalyst and its preparation method and application. The catalyst of the invention is used for catalyzing the hydrogenation of pyromellitic acid ester to prepare hydrogenated pyromellitic acid ester, the conversion rate of the substrate pyromellitic acid ester is high, and the selectivity of the target product hydrogenated pyromellitic acid ester is high.
[0012] Technical solution: The purpose of the present invention is achieved through the following technical solution:
[0013] The present invention provides a core-shell structure Ru-M@Al-SiO2 catalyst, which is composed of an active component Ru, an auxiliary active component M and an Al-SiO2 carrier; the active component Ru and the auxiliary active component M are a core layer, and the Al-SiO2 carrier is a shell; the catalyst morphology is microspherical;
[0014] The mass ratio of the Al-SiO2 carrier to the active component Ru is 1:0.02-0.05; the mass ratio of the Al-SiO2 carrier to the auxiliary active component M is 1:0.01-0.025.
[0015] Preferably, the auxiliary active component M is one of transition metals selected from W, Ni, Co and Ce.
[0016] The present invention also provides a method for preparing the core-shell structure Ru-M@Al-SiO2 catalyst, comprising the following steps:
[0017] (1) Weigh the template CTABr in distilled water, add PVP solution, and heat and stir for 0.5 to 2 hours;
[0018] (2) Add Ru(NH3)6Cl3 solution and M metal salt solution,
[0019] (3) Add ascorbic acid solution and sodium hydroxide solution, keep heating and stirring for 0.5 to 2 hours, and then drop TEOS;
[0020] (4) adding sodium aluminate solution, maintaining heating and stirring for 0.5 to 2 hours, and after the reaction is completed, centrifuging, filtering, washing, drying, calcining, and reducing to obtain Ru-M@Al-SiO2 catalyst.
[0021] Preferably, in step (2), the M metal salt is H 28 N6O 41 W 12 , any one of Ni(NO3)2·6H2O, Co(NO3)2·6H2O or Ce(NO3)2·6H2O.
[0022] Preferably, in step (1), the concentration of CTABr is 0.005-0.01 g / mL, and the concentration of PVP solution is 0.01-0.02 g / mL; in step (3), the concentration of ascorbic acid solution is 0.1-0.2 g / mL, and the concentration of sodium hydroxide solution is 0.05-0.1 g / mL; in step (4), the concentration of sodium aluminate solution is 0.01-0.02 g / mL.
[0023] Preferably, the mass ratio of TEOS to CTABr is 1:0.2-0.3; the mass ratio of TEOS to PVP is 1:0.02-0.03; the mass ratio of TEOS to Ru(NH3)6Cl3 is 1:0.002-0.005; the mass ratio of TEOS to M metal salt is 1:0.0042-0.0387; the mass ratio of TEOS to ascorbic acid is 1:0.1-0.15; the mass ratio of TEOS to sodium hydroxide is 1:0.1-0.15; and the mass ratio of TEOS to sodium aluminate is 1:0.04.
[0024] Preferably, the heating and stirring temperature is 80-90° C., and the stirring speed is 80-100 rpm / min.
[0025] The present invention also provides the use of the core-shell structure Ru-M@Al-SiO2 catalyst in catalyzing the synthesis of hydrogenated tetramethyl pyromellitic acid from tetramethyl pyromellitic acid.
[0026] The specific steps of catalyzing tetramethyl pyromellitic acid to synthesize hydrogenated tetramethyl pyromellitic acid are as follows: sequentially adding the Ru-M@Al-SiO2 catalyst, tetramethyl pyromellitic acid and solvent into a reaction kettle, replacing the air in the kettle with hydrogen, pressurizing and heating to the reaction temperature to start the reaction, and separating the catalyst by centrifugation after the reaction is completed.
[0027] Preferably, the mass ratio of tetramethyl pyromellitic acid to Ru-M@Al-SiO2 catalyst is 1:0.03-0.05; the mass volume ratio of tetramethyl pyromellitic acid to solvent is 1:20-30; the reaction temperature is 80-100°C, the hydrogen pressure is 4-6MPa, and the reaction time is 4-6h.
[0028] Preferably, the solvent is selected from one or more of methanol, ethanol, isopropanol or DMF.
[0029] Beneficial effects:
[0030] (1) The Ru-M@Al-SiO2 catalyst provided by the present invention has the advantages of high activity and easy catalyst separation. The catalyst is a noble metal catalyst, and compared with existing noble metal catalysts, the noble metal loading is lower, which reduces the production cost and is more conducive to industrial production.
[0031] (2) The preparation method of the Ru-M@Al-SiO2 catalyst provided by the present invention has simple equipment, convenient operation, mild conditions, and the core-shell structure enhances the recyclability of the catalyst. The process is environmentally friendly and conducive to large-scale production.
[0032] (3) The Ru-M@Al-SiO2 catalyst provided by the present invention is used to catalyze the synthesis of hydrogenated tetramethyl pyromellitic acid from tetramethyl pyromellitic acid, and has a high conversion rate and selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 TEM and SEM images of the Ru-W@Al-SiO2-1 catalyst in Example 1, wherein Figure (a) is the TEM image of Ru-W@Al-SiO2-1; Figure (b) is the SEM image of Ru-W@Al-SiO2-1.
[0034] Figure 2 This is a diagram of the catalyst stability evaluation results. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is described in detail below through specific embodiments, but the protection scope of the present invention is not limited to the embodiments.
[0036] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.
[0037] The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are commercially available products unless otherwise specified.
[0038] Example 1
[0039] First, weigh 0.25g of the template agent hexadecyltrimethylammonium bromide (CTABr) and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr) = 0.0075g / mL. Stir at room temperature until the solution is clear and transparent. Add 2.5mL of 0.01g / mL PVP-K60 solution to the above solution, heat to 90℃, and stir for 0.5h. Then add 0.0030g of Ru(NH3)6Cl3, 0.0042g of H 28 N6O 41 W 12 In the above solution, stir for 0.5h. Add 1mL 0.1g / mL ascorbic acid solution, keep heating and stirring at 80rpm / min for 0.5h. Then add 2mL 0.05g / mL sodium hydroxide solution, heat and stir for 0.5h. Drop 1g of tetraethyl orthosilicate TEOS, stir for 0.5h, then add 4mL 0.01g / mL sodium aluminate solution, heat and stir for 2h. The obtained product is centrifuged, filtered, washed and dried, and the dried sample is placed in a muffle furnace and calcined at 550℃ for 3h (heating rate is 2℃ / min), then placed in a muffle furnace, reduced at 400℃ for 2h in a H2 / Ar mixed gas with a hydrogen gas volume fraction of 10%, and a Ru-W@Al-SiO2 catalyst is obtained. It is recorded as Ru-W@Al-SiO2-1.
[0040] The mass ratio of Al-SiO2 to the active component Ru is 1:0.03, and the mass ratio of Al-SiO2 to the auxiliary active component W is 1:0.01.
[0041] Figure 1 TEM and SEM images of Ru-W@Al-SiO2-1 catalyst. It can be seen from the figure that the catalyst morphology is microspherical with an average particle size of 0.8μm.
[0042] Example 2
[0043] First, weigh 0.2g of the template CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr)=0.005g / mL. Stir at room temperature until the solution is clear and transparent. Add 2mL of 0.01g / mL PVP-K60 solution to the above solution, heat to 85℃, and stir for 0.5h. Then add 0.0050g of Ru(NH3)6Cl3, 0.0105g of H 28 N6O 41 W 12 In the above solution, stir for 0.5h. Add 1mL 0.15g / mL ascorbic acid solution, keep heating and stirring at 100rpm / min for 0.5h. Then add 1.5mL 0.1g / mL sodium hydroxide solution, heat and stir for 10min. Drop 1g TEOS, stir for 0.5h, then add 2mL 0.02g / mL sodium aluminate solution, heat and stir for 1h. The obtained product is centrifuged, filtered, washed and dried, and the dried sample is placed in a muffle furnace and calcined at 550℃ for 3h (heating rate is 2℃ / min), then placed in a muffle furnace, reduced at 400℃ for 2h in a H2 / Ar mixed gas with a hydrogen gas volume fraction of 10%, and a Ru-W@Al-SiO2 catalyst is obtained. It is recorded as Ru-W@Al-SiO2-2.
[0044] The mass ratio of Al-SiO2 to the active component Ru is 1:0.05, and the mass ratio of Al-SiO2 to the auxiliary active component W is 1:0.025.
[0045] Example 3
[0046] First, weigh 0.3g of template CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr)=0.01g / mL. Stir at room temperature until the solution is clear and transparent. Add 1.5mL of 0.02g / mL PVP-K60 solution to the above solution, heat to 80℃, and stir for 0.5h. Then add 0.0040g of Ru(NH3)6Cl3 and 0.0387g of Ni(NO3)2·6H2O to the above solution and stir for 0.5h. Add 1mL of 0.15g / mL ascorbic acid solution and heat and stir at 90rpm / min for 0.5h. Then add 1.5mL of 0.1g / mL sodium hydroxide solution and heat and stir for 0.5h. Drop 1g TEOS and stir for 0.5h, then add 4mL of 0.01g / mL sodium aluminate solution and heat and stir for 1.5h. The obtained product was centrifuged, filtered, washed and dried, and the dried sample was placed in a muffle furnace for calcination at 550°C for 3h (heating rate of 2°C / min), and then placed in a muffle furnace for reduction at 400°C for 2h in a H2 / Ar mixed gas with a hydrogen volume fraction of 10%, to obtain a Ru-Ni@Al-SiO2 catalyst, which was recorded as Ru-Ni@Al-SiO2-1.
[0047] The mass ratio of Al-SiO2 to the active component Ru is 1:0.04, and the mass ratio of Al-SiO2 to the auxiliary active component Ni is 1:0.025.
[0048] Example 4
[0049] First, weigh 0.2g of template CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr)=0.005g / mL. Stir at room temperature until the solution is clear and transparent. Add 2mL of 0.01g / mL PVP-K60 solution to the above solution, heat to 90℃, and stir for 0.5h. Then add 0.0030g of Ru(NH3)6Cl3 and 0.0232g of Ni(NO3)2·6H2O to the above solution and stir for 0.5h. Add 0.5mL of 0.2g / mL ascorbic acid solution and heat and stir at 90rpm / min for 0.5h. Then add 2.5mL of 0.05g / mL sodium hydroxide solution and heat and stir for 0.5h. Drop 1g TEOS and stir for 0.5h, then add 2mL of 0.02g / mL sodium aluminate solution and heat and stir for 1h. The obtained product was centrifuged, filtered, washed and dried, and the dried sample was placed in a muffle furnace for calcination at 550°C for 3h (heating rate of 2°C / min), and then placed in a muffle furnace for reduction at 400°C for 2h in a H2 / Ar mixed gas with a hydrogen volume fraction of 10%, to obtain a Ru-Ni@Al-SiO2 catalyst, which was recorded as Ru-Ni@Al-SiO2-2.
[0050] The mass ratio of Al-SiO2 to the active component Ru is 1:0.03, and the mass ratio of Al-SiO2 to the auxiliary active component Ni is 1:0.015.
[0051] Example 5
[0052] First, weigh 0.25g of template CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr)=0.0075g / mL. Stir at room temperature until the solution is clear and transparent. Add 2.5mL of 0.01g / mL PVP-K60 solution to the above solution, heat to 80℃, and stir for 0.5h. Then add 0.0020g of Ru(NH3)6Cl3 and 0.0154g of Co(NO3)2·6H2O to the above solution and stir for 15min. Add 1mL of 0.1g / mL ascorbic acid solution and heat and stir at a speed of 100rpm / min for 0.5h. Then add 2mL of 0.05g / mL sodium hydroxide solution and heat and stir for 0.5h. Drop 1g TEOS and stir for 0.5h, then add 4mL of 0.01g / mL sodium aluminate solution and heat and stir for 2h. The obtained product was centrifuged, filtered, washed and dried, and the dried sample was placed in a muffle furnace for calcination at 550°C for 3h (heating rate of 2°C / min), and then placed in a muffle furnace for reduction at 400°C for 2h in a H2 / Ar mixed gas with a hydrogen volume fraction of 10%, to obtain a Ru-Co@Al-SiO2 catalyst, which was recorded as Ru-Co@Al-SiO2-1.
[0053] The mass ratio of Al-SiO2 to the active component Ru is 1:0.02, and the mass ratio of Al-SiO2 to the auxiliary active component Co is 1:0.01.
[0054] Example 6
[0055] First, weigh 0.3g of template CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr)=0.01g / mL. Stir at room temperature until the solution is clear and transparent. Add 1.5mL of 0.02g / mL PVP-K60 solution to the above solution, heat to 90℃, and stir for 0.5h. Then add 0.0040g of Ru(NH3)6Cl3 and 0.0309g of Co(NO3)2·6H2O to the above solution and stir for 1h. Add 1mL of 0.15g / mL ascorbic acid solution and heat and stir at 80rpm / min for 1h. Then add 1.5mL of 0.1g / mL sodium hydroxide solution and heat and stir for 10min. Drop 1g TEOS and stir for 0.5h, then add 4mL of 0.01g / mL sodium aluminate solution and heat and stir for 0.5h. The obtained product was centrifuged, filtered, washed and dried, and the dried sample was placed in a muffle furnace for calcination at 550°C for 3h (heating rate was 2°C / min), and then placed in a muffle furnace for reduction at 400°C for 2h in a H2 / Ar mixed gas with a hydrogen volume fraction of 10%, to obtain a Ru-Co@Al-SiO2 catalyst, which was recorded as Ru-Co@Al-SiO2-2.
[0056] The mass ratio of Al-SiO2 to the active component Ru is 1:0.04, and the mass ratio of Al-SiO2 to the auxiliary active component Co is 1:0.02.
[0057] Example 7
[0058] First, weigh 0.2g of template CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr)=0.005g / mL. Stir at room temperature until the solution is clear and transparent. Add 2.5mL of 0.01g / mL PVP-K60 solution to the above solution, heat to 85℃, and stir for 0.5h. Then add 0.0030g of Ru(NH3)6Cl3 and 0.0145g of Ce(NO3)2·6H2O to the above solution and stir for 0.5h. Add 1mL of 0.1g / mL ascorbic acid solution and heat and stir at 90rpm / min for 0.5h. Then add 2mL of 0.05g / mL sodium hydroxide solution and heat and stir for 10min. Drop 1g TEOS and stir for 0.5h, then add 2mL of 0.02g / mL sodium aluminate solution and heat and stir for 2h. The obtained product was centrifuged, filtered, washed and dried, and the dried sample was placed in a muffle furnace for calcination at 550°C for 3h (heating rate of 2°C / min), and then placed in a muffle furnace for reduction at 400°C for 2h in a H2 / Ar mixed gas with a hydrogen volume fraction of 10%, to obtain a Ru-Ce@Al-SiO2 catalyst, which was recorded as Ru-Ce@Al-SiO2-1.
[0059] The mass ratio of Al-SiO2 to the active component Ru is 1:0.03, and the mass ratio of Al-SiO2 to the auxiliary active component Ce is 1:0.015.
[0060] Example 8
[0061] First, weigh 0.25g of template CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr)=0.0075g / mL. Stir at room temperature until the solution is clear and transparent. Add 1.5mL of 0.02g / mL PVP-K60 solution to the above solution, heat to 90℃, and stir for 0.5h. Then add 0.0050g of Ru(NH3)6Cl3 and 0.0194g of Ce(NO3)2·6H2O to the above solution and stir for 0.5h. Add 1mL of 0.15g / mL ascorbic acid solution and heat and stir at a speed of 100r / min for 0.5h. Then add 1.5mL of 0.1g / mL sodium hydroxide solution and heat and stir for 0.5h. Drop 1g TEOS and stir for 0.5h, then add 4mL of 0.01g / mL sodium aluminate solution and heat and stir for 1.5h. The obtained product was centrifuged, filtered, washed and dried, and the dried sample was placed in a muffle furnace for calcination at 550°C for 3h (heating rate of 2°C / min), and then placed in a muffle furnace for reduction at 400°C for 2h in a H2 / Ar mixed gas with a hydrogen volume fraction of 10%, to obtain a Ru-Ce@Al-SiO2 catalyst, which was recorded as Ru-Ce@Al-SiO2-2.
[0062] The mass ratio of Al-SiO2 to the active component Ru is 1:0.05, and the mass ratio of Al-SiO2 to the auxiliary active component Ce is 1:0.02.
[0063] Comparative Example 1
[0064] First, add 0.0050g of Ru(NH3)6Cl3 and 0.0194g of Ce(NO3)2·6H2O to water and stir for 0.5h. Add 1mL of 0.15g / mL ascorbic acid solution and heat and stir for 0.5h at a speed of 100r / min. Then add 1.5mL of 0.1g / mL sodium hydroxide solution and heat and stir for 0.5h. Drop 1g TEOS and stir for 0.5h, then add 4mL of 0.01g / mL sodium aluminate solution and heat and stir for 2h. The obtained product is centrifuged, filtered, washed and dried. The dried sample is placed in a muffle furnace and calcined at 550℃ for 3h (heating rate is 2℃ / min), then placed in a muffle furnace and reduced at 400℃ for 2h in a H2 / Ar mixed gas with a hydrogen volume fraction of 10% to obtain a Ru-Ce@Al-SiO2 catalyst. It is recorded as Ru-Ce@Al-SiO2-Comparison 2.
[0065] The mass ratio of Al-SiO2 to the active component Ru is 1:0.05, and the mass ratio of Al-SiO2 to the auxiliary active component Ce is 1:0.02.
[0066] Catalyst performance evaluation:
[0067] The Ru-M@Al-SiO2 catalyst prepared in Examples 1-8 and the catalyst prepared in the comparative example were used to catalyze the synthesis of hydrogenated tetramethyl pyromellitic acid from tetramethyl pyromellitic acid.
[0068] Application Example 1
[0069] 1.0g of tetramethyl pyromellitic acid raw material, 0.04g of Ru-W@Al-SiO2-1 catalyst and 25.00g of isopropanol solvent were weighed in sequence, i.e., the raw material to catalyst mass ratio was 1:0.04, the raw material mass to solvent mass ratio was 1:25, and added to a high-pressure reactor, hydrogen was used to replace the air in the reactor 3 times, hydrogen was filled into the reactor to a pressure of 6MPa, the stirring speed was adjusted to 600r / min, the temperature was increased to a reaction temperature of 100°C, the reaction was started, the reaction was carried out for 5h, and the catalyst was separated by centrifugation after the reaction was completed. The liquid obtained by the reaction was analyzed by liquid chromatography, and the conversion rate was 99.31% and the selectivity was 99.16%.
[0070] Application Example 2
[0071] 1.0g of tetramethyl pyromellitic acid raw material, 0.03g of Ru-W@Al-SiO2-2 catalyst and 30.00g of ethanol solvent were weighed in sequence, that is, the mass ratio of raw material to catalyst was 1:0.03, and the mass ratio of raw material to solvent was 1:30, and added to a high-pressure reactor. The air in the reactor was replaced with hydrogen 3 times, and hydrogen was filled into the reactor to a pressure of 5MPa. The stirring speed was adjusted to 600r / min, and the temperature was increased to a reaction temperature of 90°C. The reaction was started and the reaction lasted for 4h. After the reaction was completed, the catalyst was separated by centrifugation. The liquid obtained by the reaction was analyzed by liquid chromatography, and the conversion rate was 99.26% and the selectivity was 98.34%.
[0072] Application Example 3
[0073] 1.0g of tetramethyl pyromellitic acid raw material, 0.04g of Ru-Ni@Al-SiO2-1 catalyst and 30.00g of methanol solvent were weighed in sequence, that is, the mass ratio of raw material to catalyst was 1:0.04, and the mass ratio of raw material to solvent was 1:30, and added to a high-pressure reactor. The air in the reactor was replaced with hydrogen three times, and hydrogen was filled into the reactor to a pressure of 4MPa. The stirring speed was adjusted to 600r / min, and the temperature was increased to a reaction temperature of 80°C. The reaction was started and the reaction lasted for 5h. After the reaction was completed, the catalyst was separated by centrifugation. The liquid obtained by the reaction was analyzed by liquid chromatography, and the conversion rate was 99.46% and the selectivity was 99.03%.
[0074] Application Example 4
[0075] Weigh 1.0g of tetramethyl pyromellitic acid raw material, 0.05g of Ru-Ni@Al-SiO2-2 catalyst and 20.00g of isopropanol solvent in sequence, that is, the mass ratio of raw material to catalyst is 1:0.05, and the mass ratio of raw material to solvent is 1:20, and add them into a high-pressure reactor. Use hydrogen to replace the air in the reactor 3 times, fill the reactor with hydrogen to a pressure of 5MPa, adjust the stirring speed to 600r / min, increase the temperature to the reaction temperature of 90℃, start the reaction, react for 4h, and separate the catalyst by centrifugation after the reaction. The liquid obtained by the reaction was analyzed by liquid chromatography, and the conversion rate was 98.92% and the selectivity was 99.10%.
[0076] Application Example 5
[0077] Weigh 1.0g of tetramethyl pyromellitic acid raw material, 0.05g of Ru-Co@Al-SiO2-1 catalyst and 25.00g of isopropanol solvent in sequence, that is, the raw material to catalyst mass ratio is 1:0.05, the raw material mass to solvent mass ratio is 1:25, add to the high-pressure reactor, use hydrogen to replace the air in the reactor 3 times, fill the reactor with hydrogen to a pressure of 6MPa, adjust the stirring speed to 600r / min, increase the temperature to the reaction temperature of 100℃, start the reaction, react for 6h, and separate the catalyst by centrifugation after the reaction is completed. The liquid obtained by the reaction was analyzed by liquid chromatography, and the conversion rate was 98.16% and the selectivity was 97.35%.
[0078] Application Example 6
[0079] 1.0g of tetramethyl pyromellitic acid raw material, 0.03g of Ru-Co@Al-SiO2-2 catalyst and 20.00g of DMF solvent were weighed in sequence, that is, the mass ratio of raw material to catalyst was 1:0.03, and the mass ratio of raw material to solvent was 1:20, and added to a high-pressure reactor. The air in the reactor was replaced with hydrogen 3 times, and hydrogen was filled into the reactor to a pressure of 5MPa. The stirring speed was adjusted to 600r / min, and the temperature was increased to a reaction temperature of 90°C. The reaction was started and reacted for 5h. After the reaction was completed, the catalyst was separated by centrifugation. The liquid obtained by the reaction was analyzed by liquid chromatography, and the conversion rate was 97.48% and the selectivity was 98.12%.
[0080] Application Example 7
[0081] 1.0g of tetramethyl pyromellitic acid raw material, 0.04g of Ru-Ce@Al-SiO2-1 catalyst and 30.00g of methanol solvent were weighed in sequence, i.e., the mass ratio of raw material to catalyst was 1:0.04, and the mass ratio of raw material to solvent was 1:30, and added to a high-pressure reactor. The air in the reactor was replaced with hydrogen 3 times, and hydrogen was filled into the reactor to a pressure of 5MPa. The stirring speed was adjusted to 600r / min, the temperature was increased to a reaction temperature of 100°C, and the reaction was started for 6h. After the reaction was completed, the catalyst was separated by centrifugation. The liquid obtained by the reaction was analyzed by liquid chromatography, and the conversion rate was 98.85% and the selectivity was 98.77%.
[0082] Application Example 8
[0083] Weigh 1.0g of tetramethyl pyromellitic acid raw material, 0.03g of Ru-Ce@Al-SiO2-2 catalyst and 25.00g of isopropanol solvent in sequence, that is, the mass ratio of raw material to catalyst is 1:0.03, and the mass ratio of raw material to solvent is 1:25, and add them into a high-pressure reactor. Use hydrogen to replace the air in the reactor 3 times, fill the reactor with hydrogen to a pressure of 4MPa, adjust the stirring speed to 600r / min, increase the temperature to a reaction temperature of 80℃, start the reaction, react for 4h, and separate the catalyst by centrifugation after the reaction is completed. The liquid obtained by the reaction was analyzed by liquid chromatography, and the conversion rate was 99.37% and the selectivity was 99.24%.
[0084] The catalyst separated was recycled according to the above reaction method to investigate the stability of the catalyst. Figure 2 As shown in the figure, it can be seen that the conversion rate can still reach about 90% after the catalyst is recycled for 5 times.
[0085] Application Example 9
[0086] Weigh 1.0g of tetramethyl pyromellitic acid raw material, 0.03g of Ru-Ce@Al-SiO2-comparison 2 catalyst and 25.00g of isopropanol solvent in sequence, that is, the mass ratio of raw material to catalyst is 1:0.03, and the mass ratio of raw material to solvent is 1:25, and add them into a high-pressure reactor. Use hydrogen to replace the air in the reactor 3 times, fill the reactor with hydrogen to a pressure of 4MPa, adjust the stirring speed to 600r / min, increase the temperature to a reaction temperature of 80°C, start the reaction, react for 4h, and separate the catalyst by centrifugation after the reaction is completed. The liquid obtained by the reaction was analyzed by liquid chromatography, and the conversion rate was 43.25% and the selectivity was 96.28%.
[0087] The experimental results of each application example are shown in Table 1:
[0088] Table 1 Application example experimental results
[0089]
[0090] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention as defined in the appended claims.
Claims
1. A core-shell structure Ru-M@Al-SiO2 catalyst, characterized in that: It consists of an active component Ru, an auxiliary active component M and an Al-SiO2 carrier; the active component Ru and the auxiliary active component M are the core layer, and the Al-SiO2 carrier is the shell; the catalyst morphology is microspherical; The mass ratio of the Al-SiO2 carrier to the active component Ru is 1:0.02-0.05; the mass ratio of the Al-SiO2 carrier to the auxiliary active component M is 1:0.01-0.
025.
2. The core-shell structure Ru-M@Al-SiO2 catalyst according to claim 1, characterized in that: The auxiliary active component M is one of transition metals selected from W, Ni, Co and Ce.
3. The method for preparing the core-shell structure Ru-M@Al-SiO2 catalyst according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Weigh the template CTABr in distilled water, add PVP solution, and heat and stir for 0.5 to 2 hours; (2) Add Ru(NH3)6Cl3 solution and M metal salt solution, (3) Add ascorbic acid solution and sodium hydroxide solution, keep heating and stirring for 0.5 to 2 hours, and then drop TEOS; (4) adding sodium aluminate solution, maintaining heating and stirring for 0.5 to 2 hours, and after the reaction is completed, centrifuging, filtering, washing, drying, calcining, and reducing to obtain Ru-M@Al-SiO2 catalyst.
4. The preparation method according to claim 3, characterized in that: In step (2), the M metal salt is H 28 N6O 41 W 12 , any one of Ni(NO3)2·6H2O, Co(NO3)2·6H2O or Ce(NO3)2·6H2O.
5. The preparation method according to claim 3, characterized in that: In step (1), the concentration of CTABr is 0.005-0.01 g / mL, and the concentration of PVP solution is 0.01-0.02 g / mL; in step (3), the concentration of ascorbic acid solution is 0.1-0.2 g / mL, and the concentration of sodium hydroxide solution is 0.05-0.1 g / mL; in step (4), the concentration of sodium aluminate solution is 0.01-0.02 g / mL.
6. The preparation method according to claim 3, characterized in that: The mass ratio of TEOS to CTABr is 1:0.2-0.3; the mass ratio of TEOS to PVP is 1:0.02-0.03; the mass ratio of TEOS to Ru(NH3)6Cl3 is 1:0.002-0.005; the mass ratio of TEOS to M metal salt is 1:0.0042-0.0387; the mass ratio of TEOS to ascorbic acid is 1:0.1-0.15; the mass ratio of TEOS to sodium hydroxide is 1:0.1-0.15; and the mass ratio of TEOS to sodium aluminate is 1:0.
04.
7. The preparation method according to claim 3, characterized in that: The heating and stirring temperature is 80-90° C., and the stirring speed is 80-100 r / min.
8. Use of the core-shell structure Ru-M@Al-SiO2 catalyst according to any one of claims 1 to 2 in catalyzing the synthesis of hydrogenated tetramethyl pyromellitic acid from tetramethyl pyromellitic acid.
9. The use according to claim 8, characterized in that: The Ru-M@Al-SiO2 catalyst, tetramethyl pyromellitate and solvent are sequentially added into a reaction kettle, and the air in the kettle is replaced by hydrogen. The reaction is started after pressurization and heating to the reaction temperature. After the reaction is completed, the catalyst is separated by centrifugation. The mass ratio of tetramethyl pyromellitate to Ru-M@Al-SiO2 catalyst is 1:0.03-0.05; the mass ratio of tetramethyl pyromellitate to solvent is 1:20-30; the reaction temperature is 80-100°C, the hydrogen pressure is 4-6MPa, and the reaction time is 4-6h.
10. The use according to claim 9, characterized in that: The solvent is selected from one or more of methanol, ethanol, isopropanol or DMF.
Citation Information
Patent Citations
Benzene hydrogenation catalyst as well as preparation method and application thereof
CN102600888A
Preparation method of catalyst for hydrogenation of phthalic acid dicarboxylic ester
CN103240101A
Nickel-based core-shell structured nano catalysis material and preparation method and application thereof
CN105562001A
Synthesis method of core-shell type double-active-site catalyst and method for preparing cyclohexanone by catalyzing phenol with core-shell type double-active-site catalyst
CN111514888A
Catalyst for preparing m-xylylenediamine through continuous catalytic hydrogenation as well as preparation method and application of catalyst
CN114797817A